Asuhan Kebidanan Komprehensif pada Ny. A Usia 29 Tahun G3P2A0 di Puskesmas X - Yola Sartika; Isfaizah (Universitas Ngudi Waluyo, 2025)
Continuity of care is the provision of midwifery care starting from pregnancy, childbirth, postpartum, neonates until deciding to use family planning (KB). This aims to assist, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy until the mother uses KB. The method of midwifery care at PPuskesmas X is through home visits by providing counseling according to the mother's needs. Midwifery care provided to Mrs.